The Great Mosque of Palembang as Living Religious Heritage: Sacred Space, Institutional Transformation, and Local Islamic Identity - Tomy Wijaya; Muhammad Reza Pahlevi; M. Taofik Kurohman; Fatimah Alauwiyah; Yunus Sauman Sabin (Center for Research and Development of Religious Literature and Heritage, 2026)
Historic mosques in Indonesia are increasingly recognized as religious heritage sites whose meanings are shaped by shifting political and institutional contexts. Yet scholarship has largely concentrated on architectural preservation and contemporary religious functions, leaving long-term institutional transformations across successive political regimes underexamined. This study investigates the historical transformation of the Great Mosque of Palembang as a sacred space and living religious heritage, spanning the Palembang Darussalam Sultanate through contemporary Indonesia. A qualitative historical methodology was employed, integrating heuristics, source criticism, historical interpretation, and historiography. Data were drawn from historical literature, academic publications, Dutch colonial records, government documents, and visual materials from the KITLV Digital Collections. The findings reveal three distinct institutional transformations. During the sultanate period, the mosque functioned as a nexus of religious authority and political legitimacy, deeply embedded within royal governance structures. Under Dutch colonial administration, its political role was systematically curtailed through bureaucratic supervision and deliberate depoliticization, though it persisted as a symbol of Islamic identity and community solidarity. Following Indonesian independence, the mosque was incorporated into a modern state religious governance framework and progressively redefined as both a formal religious institution and a protected cultural heritage site. This study argues that sacred space is not inherent but historically constructed and continuously renegotiated through the interplay of religious authority, political power, collective memory, and social transformation. These findings advance scholarship on sacred space theory, religious heritage governance, and historical institutionalism within Southeast Asian Muslim societies